Perlindungan Hukum bagi Pemegang Hak Cipta Buku (Copyright) Berdasarkan Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 Tentang Hak Cipta (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The government on behalf of the public interest has broad authority to achieve the goals and objectives of accelerating development for the benefit of the nation in accordance with the mandate of the constitution. But on the other hand, the government must provide legal certainty for communities affected by land acquisition for the public interest in terms of providing compensation. In this study, the legal problem analyzed is the state's right to control land in providing legal certainty for people affected by land acquisition for the public interest. In the implementation of the settlement of compensation, it is adjusted to the estimated assessment carried out by the authorized official to determine the value or price of the land in accordance with the provisions of the legislation. The purpose of this study is to identify and analyze the existence of a protection and legal certainty for the community in the settlement of land compensation for the public interest in accordance with hierarchical rules of legislation. In this study, using the juridical – normative method through the approach of legislation. The results of this study are in the form of a juridical analysis of the settlement of land compensation for the public interest of the region.